Hunger and Food Policy of Russian Empire in Late 19th — Early 20th Centuries - A. S. Rogozhina (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The question of the causes and circumstances of overcoming hunger in Russia in the late 19th — early 20th centuries is considered in the article. Attention is paid to the analysis of historiographic material on the research topic. A review of food campaigns in Russia during the specified period is carried out. Particular attention is paid to the issue related to the circumstances of the 1891—1892 campaign, which demonstrated the inconsistency of the Food Regulations in effect in Russia since 1834. The author dwells on the issues of reforming the state food system. The main changes that took place in the state food system and associated with the approval of the food rules of 1900 are considered. The question is raised about the role of local governments in the state food policy of the period under study, as well as the perniciousness of the principle of “self-help”, which is the basis of the state food system. Attention is paid to the organization of charitable assistance to the population in the context of food campaigns. It is proved that the Russian village in the 90s of the XIX — early XX centuries was in a state of permanent food crisis due to the lack of a working model of the state food system.